Do not give your love, but Allah Practices of Support, and Emotional Security among Women in Muslim Communities in Mexico - Leyva Cortés, Samantha (2025)
This article examines how spiritual and community-based practices within Islam in Mexico function as sources of care, companionship, and emotional security for women. Based on ethnographic research conducted between 2015 and 2024 with one Muslim community in Mexico City and another in San Cristóbal de Las Casas, Chiapas, the study analyzes how this spiritual-religious worldview is embraced as a framework that provides social and emotional certainty. The analysis is framed within the affective turn, drawing on conceptual tools from Sara Ahmed and interpreting sacred experience through its emotional and embodied dimensions. In addition, following Mari Luz Esteban, the article highlights the agency of Muslim women in creating safe spaces and support networks that extend beyond Muslim women themselves, contributing to the construction of emotional communities shaped by an Islamized vision.